The Eye of a Needle: Temporary Prison Leave in Ukraine - Symkovych, Anton (European journal on criminal policy and research, 2020)
Although temporary prison leave humanises custodial punishment, offsets its negative effects, and prepares prisoners for (re)integration into wider society, its use proves to be controversial and uneven across jurisdictions. Since the collapse of the USSR, the former Soviet countries have been pursuing different criminal justice policies, liberalising some penal practices whilst retaining many punitive Soviet legacies. Through analysis of the legal provisions regulating temporary prison leave and official statistics in Ukraine, I demonstrate the apparent strain between the official policies and practice. Whilst legally available, temporary leave for prisoners in closed prisons is almost never granted in this Eastern European country. I argue that for Ukraine to reconcile the official rhetoric of rehabilitation and social reintegration of offenders and actual implementation of penal policies, the country must reverse the underlying requirements governing temporary prison leave and expand its use.